2021
DOI: 10.2196/31582
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Acceptance of a Personal Health Record: Cross-sectional Study

Abstract: Background Personal health records (PHRs) are eHealth tools designed to support patient engagement, patient empowerment, and patient- and person-centered care. Endorsement of a PHR by health care providers (HCPs) facilitates patient acceptance. As health care organizations in the Kingdom of Saudi Arabia begin to adopt PHRs, understanding the perspectives of HCPs is important because it can influence patient adoption. However, no studies evaluated HCPs’ acceptance of PHRs in the Kingdom of Saudi Ara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
2
20
1
Order By: Relevance
“…This result is consistent with findings from related studies conducted in other settings. 1 24 25 This may be due to the fact that new systems may irritate medical professionals who have a fixed, favourable opinion of ePHR systems. The availability of computers at work, continuing training and support, and knowledge sharing about eHealth technology are examples of actions that might be prioritised in order to change attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings from related studies conducted in other settings. 1 24 25 This may be due to the fact that new systems may irritate medical professionals who have a fixed, favourable opinion of ePHR systems. The availability of computers at work, continuing training and support, and knowledge sharing about eHealth technology are examples of actions that might be prioritised in order to change attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a variety of eHealth technologies have been accessible as nations have implemented eHealth efforts to support the objectives for health education and person-centred care. 1 Adoption of personal health records (PHRs) has been linked to numerous advantages, including improved patient–provider relationships, patient engagement improvements, better medication adherence, good health outcomes (such as blood pressure and glycaemic management) and higher organisational efficiencies. 2 Even though PHRs are intended to be consumer-oriented tools, simply understanding the consumer’s perspective is not enough.…”
Section: Introductionmentioning
confidence: 99%
“…Attitude is an overall evaluation of an object [ 21 ]. A positive attitude reflects positive feelings and expectations when approaching this object [ 22 ], motivating users’ engagement, particularly in using new technologies [ 23 ]. According to reinforcement theory, when individuals observed that pleasurable consequences would follow, they are more likely to engage in a behavior [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its many affordances, many implementations of eHealth services fail [ 9 - 11 ]. This might be because of resistance among health care workers [ 12 ], who correlate eHealth with threats to essential care values, fear of lost power, and professional integrity [ 13 ]. In a similar manner, eHealth can be experienced by health care professionals as taking focus from patient-centered meetings [ 14 - 16 ] and contributing to an increased amount of documentation and standardization of tasks, with lower staff influence as a result [ 17 ].…”
Section: Introductionmentioning
confidence: 99%